2001
DOI: 10.3758/bf03196401
|View full text |Cite
|
Sign up to set email alerts
|

The gender marking effect in spoken word recognition: The case of bilinguals

Abstract: There is increasing evidence that in languages that have gender agreement, a congruent gender marking usually speeds up the processing of the following noun relative to an incongruent marking (or no marking). This effect is now well established in monolinguals, but little is known about how bilinguals react to gender agreement. In this paper, we ask whether bilinguals show the same effect and whether it depends on when they acquired and started using the gender-marking language on a regular basis.In what is fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
96
2
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(116 citation statements)
references
References 15 publications
12
96
2
5
Order By: Relevance
“…This would be consistent with the idea of more "shallow," that is, less syntactically driven processing (cf. the "good enough" account by Ferreira, 2003) in L2 compared with native speakers (see Clahsen & Felser, 2006) and with behavioral studies suggesting that L2 speakers may not make use of word gender (Lew-Williams & Fernald, 2010;Scherag, Demuth, Rösler, Neville, & Röder, 2004;Guillelmon & Grosjean, 2001). However, the recategorization of trials in terms of subjective correctness for the L2 learners showed a different picture: Subjectively unexpected determiners triggered an ERP response on the subsequent noun.…”
Section: Gender Agreement Condition and The Role Of Incorrect Subjectmentioning
confidence: 99%
“…This would be consistent with the idea of more "shallow," that is, less syntactically driven processing (cf. the "good enough" account by Ferreira, 2003) in L2 compared with native speakers (see Clahsen & Felser, 2006) and with behavioral studies suggesting that L2 speakers may not make use of word gender (Lew-Williams & Fernald, 2010;Scherag, Demuth, Rösler, Neville, & Röder, 2004;Guillelmon & Grosjean, 2001). However, the recategorization of trials in terms of subjective correctness for the L2 learners showed a different picture: Subjectively unexpected determiners triggered an ERP response on the subsequent noun.…”
Section: Gender Agreement Condition and The Role Of Incorrect Subjectmentioning
confidence: 99%
“…There is also literature on the processing of gender in French, showing different effects for early and late bilinguals with L1 English (e.g., Guillelmon & Grosjean, 2001), but these are beyond the scope of the present paper.…”
mentioning
confidence: 96%
“…The RT methods include a maze task (a modified word-by-word paradigm, Nicol et al 1997), naming (Guillelmon-Grosjean 2001) and lexical decision (Gurjanov et al 1985;Lukatela et al 1987;Schriefers et al 1998), whereas on-line methods include the registration of event related brain potentials (ERP) (Coulson et al 1998;Friederici et al 1999;Gunter et al 2000;Osterhout-Mobley 1995) and eye tracking studies (Deutsch-Bentin 2001;Pearlmutter et al 1999;Vainio et al 2003;2008). As both Gunter et al (2000) and Pearlmutter et al (1999) stress, by using reaction time methods important information about the time course of agreement processing remains opaque.…”
Section: Introductionmentioning
confidence: 99%